Penetuan jumlah DOP yang tepat dalam kelompok sol plastik PVC - Susilowati Susilowati; Sri Wahyuni; Irene Sri Sukaeni (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1990)
The objectivea of this study is to determine right amount of DOP content in PVC Sole Compound made from the mixture of non reclaimed PVC material and reclaimed PVC materials, in order to increase its tensile strenght, tensile stretch and elongation at break.With basic formula which contains non reclaimed PVC materials 60 phr *), reclaimed PVC materials 40 phr, epoxy 6 phr, BaCdZn 2 phr, CaCO3 10 phr, Carbon black 0,05 phr and DOP 60 phr, it can be found that the sole compound meets the SII 1103-84 “Sol Lentur cetak PVC”. The physical properties of the sole compound as tensile strength, tensile stretch and elongation at break should be ancreased anyway, because the result showed that the figures close to the minium standard.A study on preparation of sole compound mode with DOP content of 60 phr, 50 phr and 40 phr hqd been conducted. In order ti increase the physical properties of the sole compound such as tensile strength, tensile stretch ang elongation at break. After being vulcanizead, the sole then were tested in accordance with SII 1103-84 “ Sol lentur cetak PVC”.There is no significant difference in the physical properties between the addition of 60 phr DOP and 50 phr and 40 phr DOP, while the addition of 50 phr and 40 phr DOP does not significantly affect the best. An addition of 50 phr and 40 phr of DOP contet can increase the physical properties such as tensile strength, tensile stretch, elongation at break, permanent set, abrasion resistance and tear strength. The right amount of DOP wich can be added to PVC compound for sole using the mentined above is 40 phr.